Volume 2: Symposia and General Papers, Parts a and B 2002
DOI: 10.1115/fedsm2002-31192
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Cavitation in a Francis Turbine Runner by Application of 3D Inverse Design Method

Abstract: This paper describes a new design method of blade geometry for a Francis turbine runner by using a three-dimensional inverse design method and the Computational Fluid Dynamics (CFD) technique. The design objectives are the suppression of cavitation by reducing the area in which static pressure is lower than the vapor pressure while keeping the efficiency high. In the inverse design method, it is possible to optimize the static pressure distribution in the runner by controlling blade loading parameters and/or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…This blade calculation approach based on inviscid flow-tangency condition is widely used in the inviscid IDM and it can also be applied to viscous flow case by using the transpiration technique [41,42], in which the blade geometry is updated based on the calculated normal and tangential velocity according to mass conversion. Equations (8), (14), and (16) constitute the closed equations of the three-dimensional IDM, and the blade geometry is calculated in an iterate way.…”
Section: Blade Geometry Calculation Based On Flow Tangential Conditionmentioning
confidence: 99%
See 2 more Smart Citations
“…This blade calculation approach based on inviscid flow-tangency condition is widely used in the inviscid IDM and it can also be applied to viscous flow case by using the transpiration technique [41,42], in which the blade geometry is updated based on the calculated normal and tangential velocity according to mass conversion. Equations (8), (14), and (16) constitute the closed equations of the three-dimensional IDM, and the blade geometry is calculated in an iterate way.…”
Section: Blade Geometry Calculation Based On Flow Tangential Conditionmentioning
confidence: 99%
“…Normally, the low-pressure region happens at the position where the pressure load is large, and it can be suppressed by shifting the blade loading maximum to a different streamwise location. By doing this, the low-pressure region on blade surfaces can be controlled directly and effectively, and therefore the cavitation can be suppressed effectively [13,14,22] and the suction performance can be improved [48,49]. As mentioned above, the blade stacking condition (blade lean) can also have an influence on the static pressure distribution at specific positions of the impeller, and it can also be used to suppress cavitation [13,14,48].…”
Section: Suppression Of Cavitationmentioning
confidence: 99%
See 1 more Smart Citation
“…The three-dimensional inverse design method has been applied successfully to pump [12], compressor [13], and conventional hydraulic turbine [14][15][16] so far. In the inverse design of a Francis turbine, the loading distribution and the blade stacking condition (blade lean angle) are analyzed and it is found that different blade lean angles can change the pressure distribution on the blade surface, and influence the runner performances [15].…”
Section: Introductionmentioning
confidence: 99%
“…In the inverse design of a Francis turbine, the loading distribution and the blade stacking condition (blade lean angle) are analyzed and it is found that different blade lean angles can change the pressure distribution on the blade surface, and influence the runner performances [15]. In order to reduce the probability of cavitation, the blade loading at both the band and crown should be fore loaded [14]. Since the flow calculation in the three-dimensional inverse design method is based on potential flow theory with no consideration of the fluid viscosity, simulation with high fidelity [17] is necessary for the design verification.…”
Section: Introductionmentioning
confidence: 99%